Prevention of Allergy to a Major Cow's Milk Allergen by Breastfeeding in Mice Depends on Maternal Immune Status and Oral Exposure During Lactation - Adel-Patient, Karine; Bernard, Hervé; Fenaille, François; Hazebrouck, Stéphane; Junot, Christophe; Verhasselt, Valérie (Frontiers in Immunology, 2020)
Background: the high incidence of food allergy in childhood points to the need of elucidating early life factors dictating allergy susceptibility. Here, we aim to address in a mouse model how the exposure to a major cow’s milk allergen through breastmilk of mothers with different immune status influences food allergy outcome in offspring. Methods: BALB/cJ future dams were either kept naïve, or moderately or highly sensitized, or rendered fully tolerant to bovine -lactoglobulin (BLG). After mating with naïve males and delivery, mothers were orally exposed or not to BLG during the whole lactation. In order to specifically address breastmilk effects on their allergy susceptibility, pups from naïve-synchronized mothers were cross-fostered by the different groups of treated dams and lactating mothers at delivery. In some experiments, mothers kept their own pups to address a possible in utero effect. BLG antigen, BLG-specific antibodies and BLG-immune complexes were measured in breastmilk. Allergic sensitization was monitored in 6-week old offspring by determining BLG-specific antibodies in plasma and splenocytes cytokine secretion after i.p. injections of BLG/alum. Allergic reaction to oral BLG challenge was evaluated by measuring mMCP1 in plasma. Results: Offspring was protected from allergic sensitisation when nursed by highly sensitized mothers, independently of BLG exposure during lactation. Moderately sensitized dams conferred protection in offspring solely when exposed to BLG during lactation, while naïve mother did not provide any protection upon BLG exposure. The levels of protection correlated with the levels of BLG-specific antibodies and BLG-immune complex in breastmilk. There was a trend for decreased sensitisation in offspring breastfed by tolerant and exposed mothers, which was not associated with antibody transfer. Protection was not persistent and/or did not protect from an allergic reaction. No additional in utero effects were evidenced. Conclusion: our study demonstrates the strong potential of breastmilk to modulate immune response to a major cow’s milk allergen in the progeny. It highlights the importance of maternal immune status and of her consumption of the allergen during lactation in dictating the outcomes in offspring. This opens perspectives where modulating maternal immune status may increase the chance of cow’s milk allergy prevention in breastfed children.